Filogeografia de Glossophaga soricina (Pallas, 1766), baseada nos genesmitocondriais citocromo b e citocromo oxidase I - Cayo Augusto Rocha Dias (2011)
Glossophaga soricina is a nectarivorous phyllostomid bat occurring from Mexico to south Argentina. It inhabits the most different kinds of habitats, ranging from Brazilian northeastern semi-arid caatinga to the moist Amazon rainforest. In Brazil, it seems to be the most frequentfound nectar-feeding bat in field surveys. G. soricina acts as pollinator of several Neotropical plant species. Several analysis using cytochrome b and cytochrome oxidase I were performed in order to understand the phylogeographic pattern and to assess the genetic diversity of G.soricina. High haplotipic diversity and low nucleotidic diversity were registered for both markers. The results corroborate previous works, confirming the existence of two major lineages that has been separated by Andes (as reported for other bat species). Phylogenetic and Phylogeographic analyses revealed that subspecies correspond to monophyletic groups. Two subspecies appear to be constituted of two distinct lineages. The two major lineages of this species appear to bediverged between 2.59 and 5.08 million years ago, which is the same inferred time to the occurrence of geological events that gave Andes their current altitudinal configuration. The other minor lineages originated in Pleistocene, an epoch when changes in climate were accompaniedby changes in ecosystems and sea levels that have led to phenomena such as dispersal and vicariance, both related to intraspecific diversification in G. soricina.